Pengembangan Buku Panduan Pelatihan Keterampilan Manajemen Konflik Melalui Bimbingan Berbasis Four Cs - Ari Yoga Pratama; Muslihati Muslihati; IM Hambali (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The purpose of this research is to produce a training guide product that meets the acceptance criteria. This study uses the ADDIE model research design. The data obtained in the form of quantitative data include aspects of accuracy, utility, propriety, and feasibility. The research subjects are BK experts, media experts, and potential users. The results show that the results from BK experts have a validity index of 1